Pengaruh E-service quality dan Digital After-Sales service terhadap Repurchase intention melalui Customer satisfaction RedSeller RedDoorz - Naufal Zamzami; Fresha Kharisma; Achmad Fitro; Ratih Amelia (Universitas Ngudi Waluyo, 2026)
The advancement of digital commerce requires e-commerce platforms to continuously improve service quality to maintain customer satisfaction and encourage repurchase intention. This study aims to examine the effects of E-service quality and Digital After-Sales service on Customer satisfaction and Repurchase intention among RedSeller RedDoorz agents. A quantitative approach was employed using the SEM-PLS method (SmartPLS 4) with 162 respondents selected through purposive sampling. The results indicate that E-service quality has a positive and significant effect on both Customer satisfaction and Repurchase intention. In contrast, Digital After-Sales service does not have a significant effect on Customer satisfaction but has a positive and significant effect on Repurchase intention. Customer satisfaction is also found to have a positive and significant effect on Repurchase intention. Furthermore, Customer satisfaction does not mediate the relationship between E-service quality and Repurchase intention, nor the relationship between Digital After-Sales service and Repurchase intention. These findings suggest that customers' repurchase intention toward RedSeller is influenced more directly by digital service quality and after-sales service than through customer satisfaction. Therefore, RedDoorz should continuously enhance its e-service quality and strengthen effective after-sales support to encourage sustainable service usage and customer retention. Abstrak Kemajuan perdagangan digital mengharuskan platform e-commerce untuk terus meningkatkan kualitas layanan guna mempertahankan kepuasan pelanggan dan mendorong niat pembelian kembali. Penelitian ini bertujuan menganalisis pengaruh E-service quality dan Digital After-Sales service terhadap Customer satisfaction serta Repurchase intention pada agen RedSeller RedDoorz. Penelitian menggunakan pendekatan kuantitatif dengan metode SEM-PLS (SmartPLS 4) terhadap 162 responden yang dipilih menggunakan teknik purposive sampling. Hasil penelitian menunjukkan bahwa E-service quality berpengaruh positif dan signifikan terhadap Customer satisfaction dan Repurchase intention. Sebaliknya, Digital After-Sales service tidak berpengaruh signifikan terhadap Customer satisfaction, namun berpengaruh positif dan signifikan terhadap Repurchase intention. Customer satisfaction juga terbukti berpengaruh positif dan signifikan terhadap Repurchase intention. Selain itu, Customer satisfaction tidak mampu memediasi pengaruh E-service quality maupun Digital After-Sales service terhadap Repurchase intention. Temuan ini menunjukkan bahwa niat pembelian kembali pelanggan RedSeller lebih banyak dipengaruhi secara langsung oleh kualitas layanan digital dan layanan purna jual dibandingkan melalui mekanisme kepuasan pelanggan. Oleh karena itu, RedDoorz perlu terus meningkatkan kualitas e-service dan efektivitas layanan after-sales untuk mendorong penggunaan layanan secara berkelanjutan.